1989
DOI: 10.1128/mcb.9.12.5350
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an upstream activation sequence and other cis-acting elements required for transcription of COX6 from Saccharomyces cerevisiae.

Abstract: Transcription of Saccharomyces cerevisiae COX6, the nuclear gene for subunit VI

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
22
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…address the question, we studied COX6, (25,26) and CYCI (11), the genes that encode cytochrome c oxidase subunit VI and iso-1-cytochrome c, respectively. Previous studies demonstrated that the transcription of both genes is glucose repressible in conjunction with the product of the HAP2 gene (11,23). We report here that SNFI and SSN6 are also required for the release from glucose repression of COX6 and CYC1 and that they affect the transcription of these genes in a manner analogous to the way that they regulate SUC2.…”
mentioning
confidence: 53%
See 4 more Smart Citations
“…address the question, we studied COX6, (25,26) and CYCI (11), the genes that encode cytochrome c oxidase subunit VI and iso-1-cytochrome c, respectively. Previous studies demonstrated that the transcription of both genes is glucose repressible in conjunction with the product of the HAP2 gene (11,23). We report here that SNFI and SSN6 are also required for the release from glucose repression of COX6 and CYC1 and that they affect the transcription of these genes in a manner analogous to the way that they regulate SUC2.…”
mentioning
confidence: 53%
“…To corroborate these observations, we transformed both strains with a high-copy-number COX6-lacZ fusion plasmid, pMC61L (23,24), that has 1.5 kilobase pairs of the COX6 upstream DNA and the first 21 codons of COX6 fused to the coding region of the Escherichia coli lacZ gene encoding P-galactosidase. Expression of the COX6-lacZ fusion gene carried on this plasmid is glucose repressible and requires heme and HAP2 in a way that mimics that of the copy of COX6 carried on the chromosome (23).…”
mentioning
confidence: 99%
See 3 more Smart Citations